The semantic features of English proverbs with the basic lexeme man (Diversity Research: Journal of Analysis and Trends, 2025)
Proverbs are studied not only as a means of communication but, first and foremost, as a tool for understanding the national world of other peoples, as they carry cultural information and express the national character of people. Proverbs reflect the philosophy and psychology of people, providing an opportunity to penetrate into another world and discover its most significant national values. They have a didactic meaning, characterized by conciseness of form and completeness of thought. Proverbs, as a type of paremial cliché, are a cultural heritage of the people, used in the appropriate language-speech situation. They are marked by imagery, vividness, enrich the speech of the speaker and writer, and evoke feelings of awe, surprise, sadness and other feelings and emotions of the listener